PERAN LIKUIDITAS DALAM ASSET PRICING DI BURSA EFEK INDONESIA - Dwiputri, Catherine; Nugroho, Vina Christina (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
Purpose of this study is to obtain empirical evidence about the role of liquidity in asset pricing in the Indonesian stock market. This study compares the role of liquidity as a characteristic of stocks and liquidity as a source of systematic risk. This study uses a total of 280 sample companies listed on the Indonesia Stock Exchange during the period 2006 - 2016. In measuring liquidity, this study uses the proportion of zero returns and because liquidity predicts future returns and also moves according to the past. For this reason it is necessary to have innovations to avoid stationarity issues because of the high persistence in liquidity so we use ARMA structure in the portfolio as data analysis method. Data processing was performed using the Fama-Macbeth (1973) model. The results of this study prove that market liquidity has a negative influence on stock returns on the Indonesian market. Thus, the role of liquidity as a systematic risk has an effect on asset pricing on the Indonesian stock market.